Examining the relationship between binge eating and coping strategies and the definition of binge eating in a sample of spanish adolescents - Sierra Baigrie, Susana; Lemos Giráldez, Serafín (The Spanish Journal of Psychology, 2008)
The present study had two major goals: to explore the relationship between binge eating and coping strategies in a sample of Spanish adolescents and to examine the adolescents’ concept of binge eating. Two hundred and fifty-nine adolescents from a secondary school completed the Adolescent Coping Scale (ACS; Frydenberg & Lewis, 1993) and the Bulimic Investigatory Test, Edinburgh (BITE; Henderson & Freeman, 1987), as well as additional questions regarding the binge eating episodes. The results show that the adolescents who reported binge eating used more avoidance coping strategies than those who did not engage in this behavior. Adolescents took into account mainly the amount of food eaten when defining a binge with few of them mentioning loss of control in their descriptions. The results of the study have implications for the prevention of this behavior. The development of constructive ways for solving daily problems and coping with stressors may be a possible prevention strategy for this behaviour in adolescence.